Análisis de las técnicas de deshidratación para manzana (Golden delicious) y mora (Rubus glaucus) producidas en el Cantón Cevallos. - Escobar Vega, Bryan David (2020)
The fruits produced in the Cevallos canton, such as blackberry (Rubus glaucus) and apple (Golden delicious), is the primary economic income of several farmers. In blackberry, excessive production produces excessive commercialization, while in apple at being a deciduous product, they cause waste, thereby making waste of their products. At the moment, there are different techniques for dehydration. Therefore a specific analysis was carried out, which helps the conservation of these products, which was chosen the lyophilization method, having a water elimination of 99% compared to other methods. The lyophilization preserves its organoleptic structure, such as vitamins and minerals contributing to this study. Since the moisture content of blackberry has 86.53% and apple 84.40%, the survey carried out aims to take advantage of 14% of apple production and 8.16% of blackberry at the provincial level Tungurahua for conservation. This study is based on information collected to determine a postharvest technique to exemplify the canton's fruits' conservation. In addition to this, it is wanted to promote the cultivation of apples and blackberries in the locality, for a new project in the future, to open new fields of work and research provided by said study to obtain by-products that favor local producers and thus make better use of it.